Neoantigens Generated by Individual Mutations and Their Role in Cancer Immunity and Immunotherapy - Efremova, Mirjana; Finotello, Francesca; Rieder, Dietmar; Trajanoski, Zlatko (Frontiers in Immunology, 2017)
Recent preclinical and clinical studies have proved the long-standing hypothesis that tumors elicit adaptive immune responses and that the antigens driving effective T cell response are neoantigens, i.e. peptides that are generated from somatically mutated genes. Hence, the characterization of neoantigens and the identification of the immunogenic ones are of utmost importance for improving cancer immunotherapy and broadening its efficacy to a larger fraction of patients. In this review, we first introduce the methods used for the quantification of neoantigens using next-generation sequencing (NGS) data and then summarize results obtained using these tools to characterize the neoantigen landscape in solid cancers. We then discuss the importance of neoantigens for cancer immunotherapy using checkpoint blockers, vaccination, and adoptive T cell transfer. Finally, we give an overview over emerging aspects in cancer immunity including tumor heterogeneity and immunoediting, and give an outlook on future prospects.